2016
DOI: 10.3892/ijo.2016.3373
|View full text |Cite
|
Sign up to set email alerts
|

Scrophularia orientalis extract induces calcium signaling and apoptosis in neuroblastoma cells

Abstract: Effective neuroblastoma (NB) treatments are still limited despite treatment options available today. Therefore, this study attempted to identify novel plant extracts that have anticancer effects. Cytotoxicity and increased intracellular calcium levels were determined using the Sulforhodamine B (SRB) assay and Fluo4-AM (acetoxymethyl) staining and fluorescence microscopy in NB cells in order to screen a library of plant extracts. The current study examined the anticancer effects of a dichloromethane extract fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…Baicalin, a phytochemical component of Scutellaria baicalensis Georgi has widespread applications as anti-inflammatory, anti-hepatitis and anti-oxidation agent ( 11 , 20 , 21 ). Furthermore, the anti-cancer effect of baicalin has also been previously documented ( 22 ). The present study aimed to explore the effects of baicalin on ovarian cancer cells and analyze the mechanisms underlining the observed effects.…”
Section: Discussionmentioning
confidence: 87%
“…Baicalin, a phytochemical component of Scutellaria baicalensis Georgi has widespread applications as anti-inflammatory, anti-hepatitis and anti-oxidation agent ( 11 , 20 , 21 ). Furthermore, the anti-cancer effect of baicalin has also been previously documented ( 22 ). The present study aimed to explore the effects of baicalin on ovarian cancer cells and analyze the mechanisms underlining the observed effects.…”
Section: Discussionmentioning
confidence: 87%
“…We proved that spilanthol, the main component of the Acmella extract, acted like a potent and natural diuretic in mouse by activating a mechanism based on Ca 2+ -induced inhibition of cytosolic cyclic adenosine monophosphate (cAMP) [ 1 ]. More examples are available in the literature about olive leaf extracts [ 41 ], Scrophularia orientalis [ 42 ], and Echinacea extracts [ 43 , 44 ]. For this latter extract, it has been shown that different bioactive components of Echinacea , such as alkamides (via activation of cannabinoid receptors) [ 43 ] and unknown lipophilic fractions (via direct activation of IP3 receptor) [ 44 ], are able to induce intracellular Ca 2+ peaks.…”
Section: Discussionmentioning
confidence: 99%
“…In WEHI 164 fibrosarcoma cells, a methanolic extract of this plant exhibited a significant and dose-dependent reduction of the activity of matrix metalloproteinases ( Hajiaghaee et al, 2007 ), which play a role in tissue remodeling and tumor invasion. An apolar fraction from a methanolic extract of Scrophularia orientalis L. significantly reduced the viability of neuroblastoma cells due to a loss of mitochondrial membrane integrity ( Lange et al, 2016 ). In MCF-7 breast cancer cells, weak cytotoxicity of an ethanolic extract from S. variegata was reported ( Azadmehr et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%